Dynamic behaviour of ancient freestanding multi-drum and monolithic columns subjected to horizontal and vertical excitations. Issue 120 (May 2019) - Sarhosis, V.; Baraldi, D.; Lemos, J.V.; Milani, G.
Abstract: Earthquakes represent one of the major threats to cultural heritage monuments, such as classical ancient columns. Understanding the behaviour and dynamic response of such historic structures is useful for the assessment of the conservation and rehabilitation techniques to be used for their preservation. The behaviour of ancient multi-drum and monolithic columns subjected to dynamic loads is characterized by highly nonlinearity since both rocking and sliding phenomena can occur. Analytical studies of multi-drum columns subjected to dynamic load is extremely complicated, if not impossible to perform. Nowadays, computational methods of analysis can be used to represent their dynamic response. Using a software based on the Discrete Element Method (DEM) of analysis, a typical ancient multi-drum and an equivalent in dimensions monolithic columns subjected to horizontal and combined horizontal and vertical harmonic excitations were modelled to identify the main factors affecting their stability. Different acceleration amplitude and frequency input records were applied and their role in the collapse/deformation mechanism was investigated. From the results analyses it was shown that novel structural analysis tools that extend traditional methods of structural assessment could allow engineers to understand the mechanisms that have allowed the surviving structures to avoid structural collapse and destruction during strong earthquakes. Highlights: An investigation into the dynamic response of ancient multi-drum and monolithic columns. Columns subjected to horizontal and combined horizontal and vertical harmonic excitations. DEM can be used as a tool to understanding the dynamic behaviour of ancient columns. The frequency of ground pulses significantly influence the mode of collapse. Drum joints act as a dissipation device allowing deformations between them to occur.